Unexpected linkage isomerism in chiral tetranuclear bis-tridentate (1, 2, 3-triazol-4-yl)-picolinamide (tzpa) grids. Issue 64 (23rd July 2019) - Hegarty, Isabel N.; Dalton, Hannah L.; Henwood, Adam F.; Hawes, Chris S.; Gunnlaugsson, Thorfinnur
Abstract : Two chiral [2 × 2] tetranuclear Cu II square grid complexes are prepared from a (1, 2, 3-triazol-4-yl)-picolinamide (tzpa) ligand. Linkage isomerism through the amide is observed accompanying an in situ deprotonation and Cu I → Cu II oxidation process. Abstract : The synthesis of a chiral bis-tridentate (1, 2, 3-triazol-4-yl)-picolinamide (tzpa ) ligand is described and its coordination chemistry with Cu(NO3 )2 and [Cu(MeCN)4 ]PF6 is explored in the crystalline phase as well as in solution. Chiral [2 × 2] tetranuclear square grid complexes [Cu4 (H2 1 )4 ](NO3 )8 and [Cu4 (H1)4 ](PF6 )4 were observed, and crystallographically analysed, these being linkage isomers with N4 O2 and N5 O coordination spheres, respectively. These come about by an unusual in situ amide deprotonation and coordination, which accompanies a Cu I → Cu II oxidation process.